2005
DOI: 10.1016/j.cardiores.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-? promotes atherosclerotic lesion progression in APOE*3-leiden transgenic mice

Abstract: Our data indicate that TNFalpha stimulates the formation of lesions towards an advanced phenotype, with more lesion necrosis and a lower incidence of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 47 publications
5
63
1
1
Order By: Relevance
“…A number of studies have reported that TNF␣ deficiency in hypercholesterolemic mice results in reduction of atherosclerotic plaque size without decreasing the plaque content of inflammatory cells, 14,26,31 and in line with the present observations some of these studies even observed a trend toward increased plaque inflammation in TNF␣-deficient mice. The reason why a reduced plaque inflammation was less evident in previous studies remains to be fully clarified, but it is possible that the use of a proinflammatory high-fat diet (as opposed to the chow diet used in this study) masked any possible influence of TNF␣ deficiency in those studies.…”
Section: Sclerosis Because Tnf␣supporting
confidence: 80%
“…A number of studies have reported that TNF␣ deficiency in hypercholesterolemic mice results in reduction of atherosclerotic plaque size without decreasing the plaque content of inflammatory cells, 14,26,31 and in line with the present observations some of these studies even observed a trend toward increased plaque inflammation in TNF␣-deficient mice. The reason why a reduced plaque inflammation was less evident in previous studies remains to be fully clarified, but it is possible that the use of a proinflammatory high-fat diet (as opposed to the chow diet used in this study) masked any possible influence of TNF␣ deficiency in those studies.…”
Section: Sclerosis Because Tnf␣supporting
confidence: 80%
“…Similar to IL‐1 β , TNF‐ α is a key cytokine for the recruitment and activation of inflammatory cells 9. In addition to its known ability to alter endothelial functions and increase the extent of necrosis in advanced atherosclerotic lesions,9, 21, 22 TNF‐ α is also a potent stimulator of MMP 23. MMP‐9 is a member of the gelatinase class of the metalloproteinase family and is known to play an important role in several stages of atherosclerosis 24.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, apart from the onset of atherosclerotic lesions, where TNFα is thought to delay lesion formation via impairing cholesterol accumulation in macrophages, 34 the net effect of TNFα signaling seems to promote disease. [35][36][37][38][39] This conclusion bases on the studies of atherosclerotic lesions sizes in TNFα-knockout mice and the observation of decreased vascular endothelial cell adhesiveness and decreased inflammatory factor expression in atherosclerotic plaques. In these earlier studies, [35][36][37][38][39] proatherogenic effects of TNFα were, however, related mostly to the fact that soluble TNFα promotes classical inflammatory TNFR1 signaling.…”
Section: Discussionmentioning
confidence: 99%